(تحقيق الأمن والأمان بطاعة ولي الأمر والمحافظة على مصالح الدولة) دراسة تحليلية لآيات منتخبة من سورتي البقرة وآل عمران - Ebrahim Hassan Alshehhi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2019)
Security and Safety are among the most important requirements of a decent life for men. It is a great demand for the five necessities of preservation: religion, self, mind, birth, money, and urgent humanitarian need, without development, prosperity, growth and development without it. For this purpose, the researcher sought to clarify the importance of security and safety, and to highlight the most important pillars of obedience to the guardian and the preservation of the interests of the state. The researcher used the analytical method of deductive inductive reasoning, where he recited the verses of al-Baqarah and al-'Imran and derived from them what serves the two pillars, Remote for all interpretation and distortion. It is clear through the research the effects of the realization of the pillars on the individual and society, and the corruption of many contemporary theories that clash with the Lord's approach to obedience to the guardian and the preservation of the interests of the state and make sure that security and safety is the demand of all nations and societies since eternity. Non-obedience to the guardian, and the preservation of individuals and communities to the interests of the State, are the cornerstones of the stability of States and the security of their citizens.